Environmental Tax Reform in North Macedonia : Improving Environmental and Social Outcomes from Fuel Use - World Bank (World Bank, Washington, DC, 2020)
North Macedonia continues to improve its environmental performance and the efficacy of its environmental regulation. As part of this effort, the World Bank is working with the government of North Macedonia on environmental tax reform. The government is interested in utilizing the tax system to improve environmental outcomes. This paper aims to contribute to the government’s plans by highlighting key policy options for reforming the tax system to address environmental concerns. It does this through firstly assessing the existing tax system to understand the incentives and measures in place in relation to environmental issues. It then outlines key gaps in the tax system, including in relation to the direction of environmental tax policy globally and in the European Union. As part of this analysis, the paper outlines a number of policy findings, providing suggested enhancements to the existing fiscal framework to improve environmental performance and support green industries.